2016
DOI: 10.1038/npp.2016.81
|View full text |Cite
|
Sign up to set email alerts
|

Nucleus Accumbens Acetylcholine Receptors Modulate Dopamine and Motivation

Abstract: Environmental reward-predictive cues can motivate reward-seeking behaviors. Although this influence is normally adaptive, it can become maladaptive in disordered states, such as addiction. Dopamine release in the nucleus accumbens core (NAc) is known to mediate the motivational impact of reward-predictive cues, but little is known about how other neuromodulatory systems contribute to cue-motivated behavior. Here, we examined the role of the NAc cholinergic receptor system in cue-motivated behavior using a Pavl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
90
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(97 citation statements)
references
References 49 publications
(102 reference statements)
6
90
1
Order By: Relevance
“…D1 receptors were targeted, with a D1 antagonist (SCH 23390), because of their low affinity state, which would be primarily tuned to the phasic, high concentration release of DA, documented here in vitro and in vivo (also see Cachope et al, 2012). Finally, behavior was also potently disrupted when the non-selective nACh receptor antagonist mecamylamine was infused bilaterally into the NAc at a concentration devoid of locomotor confounds (Collins et al, 2016), supporting an important role for these receptors on PFC-driven instrumental behavior, a finding that aligns with observations from our in vitro experiments and our prior work (Cachope et al, 2012, Figure 8). …”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…D1 receptors were targeted, with a D1 antagonist (SCH 23390), because of their low affinity state, which would be primarily tuned to the phasic, high concentration release of DA, documented here in vitro and in vivo (also see Cachope et al, 2012). Finally, behavior was also potently disrupted when the non-selective nACh receptor antagonist mecamylamine was infused bilaterally into the NAc at a concentration devoid of locomotor confounds (Collins et al, 2016), supporting an important role for these receptors on PFC-driven instrumental behavior, a finding that aligns with observations from our in vitro experiments and our prior work (Cachope et al, 2012, Figure 8). …”
Section: Resultssupporting
confidence: 81%
“…We further show that behavior maintained by optical stimulation of PFC terminals in the NAc is reliant upon DA D1 (Yun et al, 2004; Cheer et al, 2007) and nicotinic receptors (Crespo et al, 2008; Feduccia et al, 2014), suggesting it may recruit, at least in part, the mechanisms uncovered in our in vitro experiments for its maintenance. It is notable that nicotinic receptor blockade can, under different experimental conditions, enhance behavior as well as phasic DA concentrations in the NAc (Collins et al, 2016), thereby highlighting a precise level of influence of these neurotransmitters that is critically dependent on the neural mechanisms that motivate instrumental behavior. Thus, a possible function of eCB signaling at PFC to NAc synapses when cholinergic activity is elevated, for example when rewards are obtained (Joshua et al, 2008), may be to promote the selection of goal-directed actions toward available reinforcers in a context-and neural substrate-specific manner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of appetitive conditioning studies implicate other putative CB1- mediated targets. For example, cholinergic modulation of striatal dopamine release also mediates the expression of cue-motivated behaviors (Collins, Aitken et al 2016). Endocannabinoid regulation of striatal glutamate release drives striatal cholinergic interneurons, which in turn drive impulse-independent DA release (Exley, Clements et al 2008, Cachope, Mateo et al 2012, Threlfell, Lalic et al 2012, Mateo, Johnson et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, nAChRs located directly on dopamine terminals are in an ideal position to influence acquisition of drug self-administration and reinforcement learning. Previous work has shown that nAChRs in VTA and NAc appear to have modulatory actions on phasic dopamine signaling, as micro-infusions of MEC into the VTA attenuates (Wickham et al, 2013) while MEC into the NAc augments (Collins et al, 2016) NAc dopamine signaling in vivo . While previous literature has highlighted the importance of cholinergic signaling in both VTA and NAc to learning and reinforcement, here we show that accumbal nAChRs display wide individual variations in regard to modulation of axonal dopamine release.…”
Section: 0 Discussionmentioning
confidence: 99%